In vitro mutagenesis on patchouli (Pogostemon cablin Benth.) with gamma-ray irradiation on leaf explants - RUT NORMASARI; ESTRI LARAS ARUMINGTYAS; RURINI RETNOWATI; WAHYU WIDORETNO (Biodiversitas Journal of Biological Diversity, 2023)
Abstract. Normasari R, Arumingtyas EL, Retnowati R, Widoretno W. 2023. In vitro mutagenesis on patchouli (Pogostemon cablin Benth.) with gamma-ray irradiation on leaf explants. Biodiversitas 24: 6407-6414. Patchouli oil production in Indonesia has yet to meet international market demand, one of which is the quality of the patchouli superior seeds. Patchouli is propagated vegetatively through cuttings, causing limited variability and decreasing plant quality. In vitro mutagenesis with gamma-ray irradiation can increase plant genetic variability and produce superior patchouli plants. This study aimed to produce patchouli variants through in vitro mutagenesis by gamma-ray irradiation on patchouli leaf explants. To accomplish the research objectives mentioned above, the research stages included in vitro mutagenesis through gamma-ray irradiation, shoot regeneration, plantlet growth, and molecular analysis using SSR (Simple Sequence Repeat). Gamma-ray irradiation inhibited the growth of explants and shoot formation but could increase plantlet growth ability at low doses of 15-30 Gy. The dose of gamma-ray irradiation that caused the death of explants in fifty percent of the tested population (LD50) was 69 Gy. Molecular analysis of SSR on 50 plants regenerated from gamma-irradiated explants revealed monomorphic and polymorphic fragments compared to non-irradiated and donor plants. Primers Pca1 and Pca2 showed the highest percentage of polymorphic, with 77.3 and 50%, respectively. Gamma irradiation during in vitro culture is an alternate method for increasing genetic variety in patchouli breeding.